Enhancing Graduate Employability Through Li2U: A Digital Platform for Talent-Industry Alignment - Abu Bakar, Mohd Zamri; Halif, Mazuin Mat; Muhamed, Ariff Azly; Abd Rahim, Nur Najjah; Hassan, Mohd Faizul (Advances in Social Sciences Research Journal, 2025)
In today’s rapidly evolving job market, a significant gap has emerged between the competencies developed in higher education and those required by employers. This mismatch has led to underemployment and a lack of industry-relevant experience among graduates. To address this challenge, we propose a strategic shift towards a competency-based system in higher education. In recent years, the utilisation of mobile devices among college and university students has escalated. The utilisation of mobile devices, including smartphones and tablets, improves communication between lecturers and students as well as class activities. Mobile devices has considerable potential to transform education by enhancing the interactivity and engagement of traditional classrooms. This study introduces Li2U, a mobile application prototype designed to assist university students in efficiently locating internship opportunities, recognising that internships are crucial for professional success. There exists a correlation between internship experience and obtaining employment post-graduation. This prototype application has been created to supplant the existing manual administrative process. The significance of this research resides in the potential to expand these applications or their foundational prototypes, enabling the development of practical applications tailored to specific settings.